The Doctrine of Human Being in Indian Conversations: An Evangelical Imagination - Amritraj Joshua Paul (Religions)
The year 2025 commemorates the 1700th year of Nicaea. Ecumenical bodies across the globe are deliberating on making sense of the Nicene confession afresh in the contemporary context. At this juncture, it is appropriate to rethink the relevance of Nicaea in relation to the doctrine of human being. This article looks at the doctrine of human being, particularly in Indian conversations. Indian theologians have rendered their own understanding of human being. Notable among them are Paulos Mar Gregorios, who envisioned Sacramental Humanism, M. M. Thomas, who envisioned Secular Humanism, and Y. T. Vinayaraj, who envisions Intersubjective Humanism. Assuming the theme of ‘humanity’ to be inherent in the Nicene Creed, this article re-reads Nicaea through the lens of theologia crucis (theology of the cross), which in turn leads to a fresh imagination of the category ‘evangelical’. It repositions evangelical to mean ‘gospel-affirming’. In the light of an evangelical/gospel affirming imagination, it explores the relational nature and the critical function of doctrine in the Indian context. A relational–critical understanding of doctrine provides the scope to envision the doctrine of human being through the lens of humanitas crucis (humanity of the cross). The implications of an evangelical hermeneutic of humanitas crucis are explored in relation to the emerging digital cultural context.